Multiparametric assessment of sensorimotor abnormalities in vulnerable populations: a window of opportunity - Hirjak, Dusan; Meyer-Lindenberg, Andreas; Sambataro, Fabio; Wolf, Robert Christian (Neuroscience & biobehavioral reviews, 2022)
This commentary suggests that neuroscience research on young healthy heavy cannabis users and patients with cannabis-induced psychosis using multimodal assessment of sensorimotor dysfunction (e.g. neuroimaging, clinical rating scales, and instrumental assessments) may help to identify both biological resistance and vulnerability without constraints and confounder factors imposed by antipsychotic treatment or disease chronicity.
Gesehen am 26.08.2022